Urea Uptake and Water Retention Properties of Potassium Polyacrylate Hydrogel for Agricultural Applications - Ts. Dr. Hatika Kaco; Maizatul Husna Nasuha Mazlan; Alyasofea Nazrul Hisham; Adam Khairul Faiz; Muhammad Khairil Hakim Ismail; Mohd Shaiful Sajab; Fadzidah Mohd Idris (Malaysian Analytical Sciences Society (ANALIS), 2026)
Tier 2 (Indexed by Scopus)